1995
DOI: 10.2172/218236
|View full text |Cite
|
Sign up to set email alerts
|

AXAIRQ User`s Manual

Abstract: SAVANNAH RIVER srm Westin house Savannah River Company Alken, ! k 29808-n-l l r 2 PREPARED FOR THE US. DEPARTMENT OF ENERGY UNDER CONTRACT NO. DE-AC09-89SR18035 4. DISCLAIMER This report was prepared as an account of work sponsored by an agency of the United States Government. Neither the United States Government nor any agency thereof, nor any of themployees, makes any warranty, express or implied, or assumes any legal liability responsibility for the accuracy, completeness, or u any information, apparatus, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…Other critical interfaces in planar SOC stacks are those between the cell and the interconnect. On the fuel electrode side Ni meshes or foams can be used to ensure good adhesion and current distribution (7)(8)(9). However, the adherence between the oxygen electrode and the interconnect is more challenging.…”
Section: Introductionmentioning
confidence: 99%
“…Other critical interfaces in planar SOC stacks are those between the cell and the interconnect. On the fuel electrode side Ni meshes or foams can be used to ensure good adhesion and current distribution (7)(8)(9). However, the adherence between the oxygen electrode and the interconnect is more challenging.…”
Section: Introductionmentioning
confidence: 99%
“…A total friction welding process has seven phases, such as fast-forward, work into, preliminary top, withdrawal, friction, upset forging and fast-backward. In the AMESim mode [9][10], construction model of applying common friction welding machine hydraulic pressure system is shown in Figure 1. The main simulation parameter is set to the speed of dosing pumps 1500r/min, with the displacement 76mL/r, the pressure relief valve 15MPa, the force cylinder piston diameter 180mm, the piston rod diameter 80mm, the piston stroke 870mm, the moving parts quality 191kg.…”
Section: The Normal Friction Welder Hydraulic Force Application Systemmentioning
confidence: 99%
“…W use is the actual use of the work and W in is the total input power formula (9). When the friction welding process and the parameters are determined, W use is a constant value on base and has little contribution to the system work efficiency, so in order to improve the work efficiency of hydraulic power of friction welding system, W in must decrease from the start.…”
Section: The Hydraulic Force Application System Of Efficiency Analysismentioning
confidence: 99%
“…cerevisiae that our labs have recently generated, covering more than 13,000 compounds from the 22 RIKEN NPDepo and several NCI, NIH, and GlaxoSmithKline (GSK) compound collections. 23 Supportive of the idea that chemical-genetic interaction data provide an unbiased proxy for 24 biological functions, we found that many commonly used structural similarity measures were 25 able to predict the compounds that exhibited similar chemical-genetic interaction profiles, 26 although these measures did exhibit significant differences in performance.…”
mentioning
confidence: 99%
“…We generated, in our labs, the chemical-genetic interaction profiles for 13,524 compounds 117 from several diverse compound collections [20]. We used a subset of these screened compounds 118 that exhibited high confidence predictions for the annotated processes and biological pathways 119 based upon our chemical-genetic interaction profiles [20,22]. We included in our benchmarking 120 system two compound sets independently: (1) 826 compounds from the RIKEN Natural Product 121 Depository (NPDepo) compound collection, which we called RIKEN high confidence collection.…”
mentioning
confidence: 99%